HIKAYAT DATOE LANCANG-PUTRI KAYAN: REFLEKSI PERLAWANAN RAKYAT TERHADAP KOLONIALISME DI TANAH KALIMANTAN (HIKAYAT DATOE LANCANG-PUTRI KAYAN: THE REFLECTION OF PEOPLE’S RESISTANCE TOWARD COLONIALISM IN THE LAND OF KALIMANTAN) - Derri Ris Riana (Balai Bahasa Sulawesi Utara, 2016)
Postcolonial research in literature text will always be interested to be used to reveal many practices as a result of colonialism. Colonialism practices that had been continued between the same ethnic groups, like in Hikayat Datoe Lancang-Putri Kayan hasn’t been revealed yet. By analizing textually and using postcolonial theory, this article wants to reveal the history of Bulungan Sultanate that exposes in Hikayat Datoe Lancang-Putri Kayan toward the opposition of colonized group and colonialist and analize the opposition forms toward colonialism. The result shows that Hikayat Datoe Lancang-Putri Kayan reveals the history of Bulungan Sultanate. Postcolonial research analized colonialist and colonized group. Colonized, that is Dayak Iban is constructed as dominates, underestimates, powerful, superior, arrogant, tricky, anarchist, and cruel group. Meanwhile, the colonized group, that is Dayak Kayan Uma Afan is constructed in the position of weak, pessimist, hopeless, and follows imitates the colonialist’s track. Besides, the opposition’s forms that are done by Dayak Kayan to oppose colonialism are the preparation of physical troop, the arrangement of attack’s strategy, the construction of traps, and the fighting between etnic group leaders.